2021
DOI: 10.29328/journal.afns.1001027
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing eating disorders through the misperception of the body image and the adoption of bad eating habits in a sample of young volleyball athletes

Abstract: Objective: This preliminary study focused on the description of some dysfunctional perceptions of the body image and eating habits in a sample of young. Methods: The results obtained by 55 amateur and professional volleyball players belonging to volleyball sports clubs located in the province of Reggio Emilia were examined. The age of the sample is in a range between 11 and 44 years. The participants completed the Pisa Survey for Eating Disorders (PSED), a questionnaire aimed at examining eating behavior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that the level of competition and training experience are related to the development of eating disorders in athletes [ 75 , 76 ]. Competing at the international level generates higher level standards in athletes, so this has been determined as a high-risk factor for presenting with eating disorder symptoms with the frequency [ 77 , 78 , 79 ] due to the sports and expectative requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the level of competition and training experience are related to the development of eating disorders in athletes [ 75 , 76 ]. Competing at the international level generates higher level standards in athletes, so this has been determined as a high-risk factor for presenting with eating disorder symptoms with the frequency [ 77 , 78 , 79 ] due to the sports and expectative requirements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Beals and Manore [ 15 ] found lower body satisfaction and eating disorder symptoms among 75% of participants who participated in endurance sports. Fochesato et al [ 12 ] also reported lower body satisfaction (30% of participants) and eating disorder behaviors (16% of participants) in a cohort of female athletes in volleyball sports clubs.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that there are also sports, such as technical, power, and ball sports [ 7 ], which promote different body ideals and are not lean body oriented. However, in some studies, disordered eating and eating disorders were also found among athletes of non-lean disciplines [ 7 , 12 ]. Originally, studies investigating eating disorders among athletes focused mainly on the aesthetic and non-aesthetic division.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations